Influence of infill on the cyclic behaviour of traditional half-timbered walls - Poletti, Elisa (2013)
Half-timbered buildings represent an important historical heritage in many countries. They are diffused in various regions for different reasons, such as availability of materials, to lighten a structure, low cost and the strength they offer, and as a construction element able to resist seismic actions. This latter issue is the research topic analysed here, as half-timbered buildings have been specifically used in reconstruction plans as earthquake-resistant buildings in many countries, such as Portugal, India, Greece, etc. The aim of this paper is to study the behaviour under cyclic loading of such half-timbered walls, with typical connections, materials and geometries encountered in existing buildings. Traditionally, different types of infill could be applied to half-timbered walls depending on the country, namely brick masonry, rubble masonry, hay, mud, etc. The focus of this paper is to study and compare the seismic behaviour of the walls considering two different infill typologies, as well as the possibility of having no infill, i.e. considering only the timber frame. Cyclic test were performed on traditional walls and their behaviour was studied in terms of ultimate capacity, deformability, energy dissipation and stiffness.